Influence of High-Intense Ion Pulses on Tungsten Surface Erosion; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Shimanskii (Shymanski) V. I. Vitali Igorevich; Uglov V. V. Vladimir Vasilievich; Pigasova V. S.; Astashynski V. M.; Kuzmitski A. M.; Zhong H. W.; Zhang S. J.; Le X. Y. (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана